Sistem Deteksi Otomatis dan Self Cleaning pada Cat Litter Box - Masril, Mardhiah; Ghinaa Fadhiilah; Ruri Hartika Zain; Billy Hendrik (JURNAL QUANCOM: QUANTUM COMPUTER JURNAL, 2024)
This research discusses the development of an Automatic Detection and Self Cleaning System on a Cat Litter Box using the Wemos D1 mini microcontroller, to improve the efficiency of cat maintenance. In this context, cats as pets have psychological uniqueness closely related to humans. The litter box, as a specific place for burying cat feces and urine, requires continuous attention and maintenance to keep it clean. This research develops a device that automatically detects cats entering the litter box, and then separates the feces from the sand in the cat litter box. The feces are transferred to a container that will be weighed using a load cell. Cat owners will receive notifications on their smartphone devices through their Telegram application to dispose of the waste. The system also monitors the sand height in the storage container, and the sand dispenser will refill it to a certain limit. The development of this system is expected to provide a solution for cat owners who need to leave their pets for a certain period. This research also demonstrates positive results through testing and notifications on smartphone devices as well as display on the LCD screen in the litter box.